Enhancing Student-centered Learning through Introducing Module for STEM Development and Assessment - Al-Ansi, Abdullah M.; Al-Ansi, Ahmed (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
During Covid-19 pandemic, virtual learning has a significant role in conducting learning process in almost all educational institutions around the world. This study introduces new module of e-learning and examines recent known evaluation methods through virtual learning. Science, Technology, Engineering and Mathematics (STEM) are the most subjects facing several challenges during virtual learning based on the nature of these courses and using mathematics and related practices. Mixed method of quantitative and qualitative data analysis was adopted to conduct this study. Six expertise in pedagogical Science were chosen for interviews to investigate and develop e-learning module and a sample of 623 students were chosen to evaluate the learning module. This study developed PADA module through conducting online assessment for educators and students in selected universities in Yogyakarta, Indonesia. The module has many benefits to conduct successful virtual learning during Covid-19 pandemic and similar issues. More instructions about re-using this module have been represented as part of this study.